2022
DOI: 10.1177/14771535221093470
|View full text |Cite
|
Sign up to set email alerts
|

Visual cues to interpersonal evaluations for pedestrians

Abstract: Pedestrians need to be able to evaluate other people to support their feeling of safety. While past studies have thus investigated the degree to which road lighting supports facial identity and facial emotion evaluations, it is not yet known whether the face is the most important visual cue. Following a pilot study that indicated the importance of the ability to see the face and hands of other people, an experiment was conducted in which test participants evaluated safety when shown photographs of an approachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Rather than conducting a study in controlled experimental conditions, as is often the case, Hennig et al 2 used undisturbed field observations. Hamoodh et al 3 showed through a photograph-based experiment that the face, rather than the hands, of an approaching pedestrian is the most important visual cue in interpersonal safety evaluations during night-time. Lastly, Jedon et al 4 proposed a new theoretical framework for evaluating street lighting that includes factors previously unaccounted for, such as alertness, arousal and anxiety.…”
mentioning
confidence: 99%
“…Rather than conducting a study in controlled experimental conditions, as is often the case, Hennig et al 2 used undisturbed field observations. Hamoodh et al 3 showed through a photograph-based experiment that the face, rather than the hands, of an approaching pedestrian is the most important visual cue in interpersonal safety evaluations during night-time. Lastly, Jedon et al 4 proposed a new theoretical framework for evaluating street lighting that includes factors previously unaccounted for, such as alertness, arousal and anxiety.…”
mentioning
confidence: 99%